ANALISIS PENGARUH CITRA ELLA ORGANIC SKIN CARE TERHADAP WORD OF MOUTH POSITIF DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Ernawati, Dani Ayun Pratiwi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
The objective of the research are to analyses (1) effect image of Ella Organic Skin Care Surakarta to customer satisfaction, (2) effect image of Ella Organic Skin Care Surakarta to positive WOM, (3) Effect customer satisfaction to positive WOM, (4) effect image of Ella Organic Skin Care Surakarta to positive WOM through customer satisfaction as the mediating variable. The result reveals that (1) there is a significance effect between image of Ella Organic Skin Care Surakarta to customer satisfaction, showed p value (0,000) < 0,05, (2) there is a significance effect between image of Ella Organic Skin Care Surakarta to positive WOM showed p(0,027) < 0,05, (3) there is a significance effect between customer satisfaction to positive WOM, showed p (0,005) < 0,05, (4) there is a significance direct effect of image of Ella Organic Skin Care Surakarta to positive WOM through customer satisfaction as the mediating variable showed coefficient of the indirect effect (0,541) is greater than that coefficient of the direct effect (0,208). The conclusion of this research that all hypothesis is true. Keywords: corporate image, customer satisfaction, positive WOM